PHOTOIONIZATION OF METALS - Monroy Cárdenas, Oscar S. (2000)
The interaction of metallic solids with two simultaneous radiation fields, X-ray and laser, is investigated using non conventional theorical techniques. The gauge independent photo-ionization probability per unit time has been calculated for a valuence band electron in a metal induced by X-rays and a circularly polarized laser beam of arbitrary intensity.